Persepsi Terhadap Celebrity Endorser pada Iklan Kosmetik dan Minat Beli pada Mahasiswi - Isella Loviana; Yapsir G. Wirawan; Wanadya A.K. Dewi (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
This study was aimed to examine the correlation between perception towards celebrity endorsers in cosmetic advertisements with the interest in purchasing of a university student. The hypothesis proposed in this research was that there was a positive correlation between perception towards celebrity endorsers in cosmetic advertisements with the interest in purchasing of a university student. Subjects used in this study were 90 female students of Psychology Faculty, Islamic University of Indonesia. The ages of the Subject are between 18-21 years old. The data collection used two types of scale, namely the scale of perception towards celebrity endorsers in cosmetic advertisements and the scale of purchasing interest. Scale of perception towards celebrity endorsers in cosmetic advertisements was developed by the researcher based on aspects to the celebrity endorsers perception presented by Belch and Belch (1995), which included the aspects of credibility, attractiveness, and power. The scale of purchasing interest was developed by the researcher based on aspects of purchasing interest presented by Krech & Crutchfield, (Prasitejo, 2005), which included affective (interest), cognitive (belief), and conative (decision). The results of testing the relationship between perception towards celebrity endorsers in cosmetic advertisements with interest in purchasing showd that the perception towards celebrity endorsers in cosmetic advertisements associated with level interest in purchasing (r = 0.607 with p=0.000 (p<0.01) therefore the hypothesis was accepted). The contribution of perceptions to the celebrity endorser on cosmetics advertisement to the interest in purchasing was 36.9%.Keywords : Interest in Purchasing, Perceptions towards Celebrity Endorsers